Further evidence of humpback whale presence in deep tropical ocean during the breeding season: confirmation and extension of acoustic detections between Hawaii and Mexico - Darling, James D.; Goodwin, Beth (Frontiers in Marine Science, 2023)
During winter humpback whales converge on tropical breeding grounds characterized by shallow, warm seas. In the eastern half of the North Pacific two such breeding grounds are located along the shorelines and shallows of Mexico, and in mid-ocean around Hawaii, separated by 4,500-6,000 km of deep ocean basin. A 2018 acoustic survey by an autonomous Wave Glider from Hawaii eastward towards Mexico, at breeding ground latitudes (circa 20°N) and during peak breeding season, discovered singing whales between these locations near continuously out to mid-ocean - the first evidence of this latitudinal, tropical deep-water distribution. We report the results from a 2021 study which replicated the first half of the 2018 route and extended the survey to Isla Clarión, the westernmost breeding ground of Mexico. The portion of the 2021 survey replicating the earlier course resulted in markedly similar, near-continual detection of humpback whales from Hawaii out 2,161 km (over 1,000 nm) to mid-ocean. Detections occurred on 29 of the first 37 days eastbound from South Point Hawaii (vs. 30 of 35 days in 2018), with up to 3,000 calls a day, including multiple simultaneous singers. The 2021 extension (non-replicative portion) from mid-ocean eastward produced intermittent detections to Isla Clarión. The results, combined with recent reports of photo-identified individuals which traveled between Mexico and Hawaii in one winter season, indicate a recurring tropical offshore presence between these traditional breeding grounds - its extent and purpose to be determined.